Pengaruh Penerapan Pembelajaran Diferensiasi terhadap Keterampilan Siswa Menulis Paragraf di Kelas VII SMP Negeri 1 Parbuluan - Pontas J. Sitorus; Ance S.N. Siregar; Beslina Afriani Siagian (Journal of Language Education (JoLE), 2023)
This research aims to determine "The effect of implementing differentiated learning on students' paragraph writing skills in class VII SMP NEGERI 1 PARBULUAN". This type of research is Quantitative Experimental Research with a One group Pretest and Posttest design. The population in this research is all class VII students with a total of 180 students and the sample is class VII-4 with 30 students and class VII-5 with 30 students. 30 students were determined using the Cluster Sampling Technique. The data analysis techniques used are Normality test, Homogeneity test and Hypothesis test. After conducting research on the pretest and posttest control classes, the average pretest score was 60 with a standard deviation of -1.27 and the average score on the posttest was 77.26 and a standard deviation of -3.27 from the results of the hypothetical test in the research This table "t" test was carried out at a significance level of 5% with df = N-2. df is 30 then 28. From df 28 the significance level is processed at 5% = 1.701. Based on the calculations that have been carried out, it can be seen that tcount> ttable, namely 6.76> 1.701. Thus the null hypothesis (HO) is rejected and the hypothesis is accepted so that it is stated that the application of differentiation learning has an effect on writing ability. Keywords: Differentiated Learning, Writing Description Paragraphs, Writing Skills.